The outcomes of salvage robotic radical prostatectomy following radiation versus focal therapy: Does the primary treatment modality matter? - Alireza Ghoreifi; Lorenzo Storino Ramacciotti; Masatomo Kaneko; Luis G. Medina; Giovanni E. Cacciamani; Shiran Konganige; Manju Aron; Sarmad Sadeghi; Hossein Jadvar; Hooman Djaladat; Rene Sotelo; Mihir M. Desai; et al. (BJUI Compass)
Abstract Objectives We aim to compare salvage robotic radical prostatectomy (sRRP) for recurrent prostate cancer (PCa) after primary radiation (RT) versus focal therapy (FT). Materials and Methods Patients who underwent sRRP following primary local therapy for PCa were identified. Perioperative findings and functional/oncologic outcomes were compared in RT versus FT groups. Results Overall, 112 patients were included, with 84 receiving RT and 28 FT as primary treatment. Median age and PSA were 68 years and 5.4 ng/mL, respectively. There was one rectal injury in the RT group. The overall 90‐day complications were significantly higher in RT group (33% vs. 11%, p = 0.03). On multivariable analysis, history of RT and prolonged operative time were associated with a higher rate of 90‐day complications. The 6‐ and 12‐month continence rates were higher in FT group (50% vs. 20%, p = 0.02 and 69% vs. 33%, p = 0.03). Potency at 12 months was better preserved in FT group (46% vs. 12%, p = 0.01). On final sRRP pathology, the rates of grade group ≥ 4 (51% vs. 36%, p = 0.2), pT3 (69% vs. 75%, p = 0.6), positive nodes (30% vs. 18%, p = 0.2) and positive margins (33% vs. 39%, p = 0.5) were similar for RT versus FT, respectively. The 3‐year biochemical recurrence‐free survival was 86% for RT versus 94% for FT (p = 0.6). Conclusion sRRP for recurrent PCa after FT is associated with lower complications and higher urinary continence and potency rates than patients who received primary RT.